2016
DOI: 10.7754/clin.lab.2015.150832
|View full text |Cite
|
Sign up to set email alerts
|

Role of Presepsin for the Assessment of Acute Cholangitis Severity

Abstract: Background:Presepsin is a new emerging inflammatory biomarker. The primary purpose of this study was to elucidate the predictive usability of presepsin for severity assessment in patients with acute cholangitis (AC). Methods:A total of 119 treatment-naive patients with AC (64 males, 55 females) were enrolled in this study. Patients were classified with Grade I (mild), Grade II (moderate), or Grade III (severe) AC based on severity assessment guidelines. Presepsin concentrations were measured on admission. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…In another recent prospective study, procalcitonin was found to be increased significantly in either moderate or severe AC (28). Another inflammatory marker Presepsin was found to be significantly higher in patients with severe AC than in patients with moderate AC or with mild AC (29). In our study we found that IL-33 increased significantly in patients with moderate/severe AC who need immediate biliary drainage.…”
Section: Resultssupporting
confidence: 64%
“…In another recent prospective study, procalcitonin was found to be increased significantly in either moderate or severe AC (28). Another inflammatory marker Presepsin was found to be significantly higher in patients with severe AC than in patients with moderate AC or with mild AC (29). In our study we found that IL-33 increased significantly in patients with moderate/severe AC who need immediate biliary drainage.…”
Section: Resultssupporting
confidence: 64%
“…Although the distributions also differed by the type of infection (Figure 3), which seemed to reflect the severity of infection and organ damage, the low incidence of complications prevented us from analyzing the diagnostic superiority of presepsin between local and systematic infections, which requires further investigation. However, given that the reported median or mean values of presepsin for local infection ranged from 590 to 721 pg/mL according to a very small number of studies, 2,28 our data are reasonable.…”
Section: Discussionmentioning
confidence: 50%
“…It is an easy and effective scoring system, its usefulness has been con rmed, and it was taken over to the Updated Tokyo Guidelines for acute cholangitis and cholecystitis in 2018 [18,19]. Furthermore, PCT [6][7][8], endotoxin activity [20,21], NF-kB [22], IL-7 [23], delta-neutrophil index [24], and presepsin [25] have been reported as independent biomarkers for prognosis of acute cholangitis and PCT [6,23], endotoxin activity [20], and IL-7 [23] for bacteremia.…”
Section: Discussionmentioning
confidence: 99%